Assessing Competencies of Tourism Students through Poster Presentation: Evidence from Indonesia - Junaid, Ilham (Journal of Tourism Management Research, 2018)
This paper aims to examine the effectiveness of poster presentation in assessing the tourism students’ competencies. Three issues were investigated including the students’ responses, strengths and weaknesses and the students’ recommendation for more practical students’ learning. This research employed a case study approach (from July to December 2017) at Makassar Tourism Polytechnic, Indonesia. The study reveals that although students were worried about the implementation of poster presentation, the students were successfully participated in the examination through poster presentation. Three strengths were found including the students understand topics and sub-topics of a subject; link tourism concepts with the real context; and improve their self-confidence. This paper recommends the implementation of poster presentation for two reasons; 1) it supports the students to learn tourism concepts and issues independently; 2) it implements systematic ways including input (lecturer explains it), process (students prepare their poster), and output (students’ competencies).